Doing things their way? Food, farming and health in two Ugandan cities - Mackay, H.; Mugagga, F.; Kakooza, L.; Chiwona-Karltun, L. (Cities & Health, 2017)
This paper presents new data on urban households’ agriculture, food environments and noncommunicable disease (obesity, diabetes, hypertension) in two intermediate-sized Ugandan cities (Mbale and Mbarara). Nutrition transition theory suggests that fast-foods, eating out and supermarket shopping, together with sedentary urban lifestyles and less agricultural activity, are drivers of growing non-communicable disease burden. We explore these claims using statistics from a 2015 socio-economic and anthropometric survey of 1995 households. Results indicate that these cities are already experiencing non-communicable diseases, despite a lack of advanced food system and nutritional transitions. Surveyed households generally had low or medium dietary diversity, and a diet pattern and an agricultural practice primarily geared towards staple foods. Food transfers (mainly staples) from rural relatives were common, particularly for agricultural households. These farming households also had better income status than nonfarming households. Experience of food insecurity was relatively common. Nevertheless, high prevalence and strongly gendered patterns of obesity were identified. In contrast to some theorising of the farming practice of urban-based households, there was little evidence that such agriculture was fuelled by poverty, vulnerability or migrant status. Findings also imply that there are other drivers of epidemiologic change in these cities than those suggested by nutrition transition theory.
Keywords: Urban Uganda; Urban health; Urban food systems; Dietary diversity; Epidemiological transition; Nutrition transition